Bone marrow edema syndrome of the hip: an update on current concepts. Issue 2 (March 2016) - Ting, Chee Han; Arora, Esha; Arora, Manit
Abstract : Bone marrow edema syndrome of the hip is a rare condition that presents with self-limiting functional disability disproportionate to pain and signal changes on MRI consistent with bone marrow edema. Its etiology has not been established, but the most convincing theory implicates venous outflow obstruction from the diseased segment of bone. Bone marrow edema syndrome is a diagnosis of exclusion, following comprehensive work-up to rule out similarly presenting lesions. Once a diagnosis has been made a number of treatment strategies have been proposed, all with limited evidence. Conservative management is only supportive and involves analgesia and restricted weight bearing. Medical management with bisphosphonates and iloprost yield satisfactory results with minimal adverse effects. Alternative therapies include extracorporeal shock wave and hyperbaric oxygen therapy. Surgical core decompression offers immediate pain relief and faster recovery but may only be offered for severe, refractory disease.